Solar irradiation in diffusely enclosures with partitions - Miguel, A. F. (2012)
This paper presents an approach to obtain the income of solar irradiation within partitioned enclosures partially transparent to solar radiation. This model is mathematically exact and it is function of the outside solar irradiation, the orientation of the enclosure, the properties of the enclosure envelope, the geometry and properties of partitions. From the physical point of view it is founded on the assumption that the envelope and partitions surfaces are fully diffusive and that the radiation diffused through the atmosphere is fully isotropic. The model was applied to assess the solar irradiation at the ground of a hemicylindrical tunnel ﬁtted with inclined partitions. The results of this study demonstrate, among other things, that: (i) the solar irradiation inside the enclosure, with any cladding material and with any orientation, is mainly determined by the transmittance of the partitions and to a lesser extent by its reﬂectance, (ii) the solar radiation inside an enclosure with highly transparent partitions (i.e., transmittance > 0.5) is noticeable inﬂuenced by its orientation, but for a lower transmittance the inﬂuence of orientation becomes negligible; and (iii) to prevent the overheating within the enclosure it is advisable to install partitions with a low transmittance and a high absorptance on their surface facing downward.